ANALISIS PEMBELAJARAN TEMATIK TERHADAP PENGEMBANGAN CIVIC DISPOSITION SISWA KELAS V GUGUS SEKOLAH II KECAMATAN SUKOREJO KABUPATEN PASURUAN: Array - Nabillah Alawiyah Shohib; Mujtahidin Mujtahidin; Umi Hanik (Citra Dharma Cindekia, 2022)
For This study aims to describe the implementation of thematic learning to development of civic disposition through and the obstacles encountered in the school group II, Sukorejo sub-district, Pasuruan district. This study uses a qualitative approach to the type of phenomenology. The subjects in this study were students in class V, class V teachers, and school principals. Data collection uses observation, interview, and documentation techniques. The results showed that: First; Implementation of thematic learning in Gugus Sekolah II, Sukorejo sub-district, Pasuruan district, developed 8 indicators of citizenship character namely; (1) moral responsibility, (2) self-discipline, (3) respecting the dignity and human dignity of each individual, (4) community spirit; (5) manners; (6) respect for the rule of law; (7) critical thinking; (8) and desire to listen. Second; obstacles in analysing the implementation of thematic learning towards the development of civic disposition, namely: (1) difficulty in conducting assessments by class teachers, and (2) lack of support and attention from the environment of students.